Upaya Dinas Perhubungan dalam Peningkatan Pemungutan Retribusi Terminal Kota Jepara - Subadriyah Subadriyah; Muhammad Khairul Hakim (Jurnal Rekognisi Akuntansi, 2017)
The purpose of this study was to determine the terminal retribution collection system in Jepara district, the efforts of the transportation service in increasing Jepara city terminal retribution collection and the inhibiting and supporting factors in carrying out Jepara city terminal retribution collection. This type of research is descriptive qualitative. Data collection techniques in this study were conducted by means of interviews, documentation and observation with interactive model data analysis. The results of the study can be seen that the terminal retribution collection system is carried out by two retribution collectors who stand in front of the entrance and exit of the terminal, by pulling each transport that enters the terminal according to the rates listed on the ticket and is given a TPR (sign of payment of retribution) or in accordance with the SOP for withdrawal of terminal retribution. The inhibiting and supporting factors in the implementation of the Jepara city terminal levy collection are the reduced number of vehicles, declining public transport service users, government regulations on mass transportation that have not been implemented properly, the ease with which people get / have two-wheeled transportation and private cars, community human resources who are low. The supporting factors are terminal human resources/terminal officers and the collection is carried out based on regional regulation number 22 of 2011.